AI Competency Among Students of the Bachelor of Food Technology Program at UTHM - Nordin, Nur Farah 'Adilah; Norhasyimah Hamzah (Research and Innovation in Technical and Vocational Education and Training, 2025)
The rapid development of the Fourth Industrial Revolution has introduced artificial intelligence (AI) into various sectors, including higher education and the food service industry. However, AI competency among students in the Bachelor of Food Service Technology program at UTHM remains critically low. Students show limited understanding of AI applications, ethics, and system design, compounded by digital gaps and an over-reliance on AI without ethical considerations. This study aims to determine students’ level of AI competency and examine the relationships between human-centered thinking, AI ethics, AI techniques and applications, and AI system design with their AI competency. A quantitative survey method was employed, involving 80 students, and data were analyzed using descriptive and inferential statistics, including Spearman correlation. Findings show students demonstrated a high level of AI competency (mean = 3.88, SD = 0.78), with the highest mean in techniques and applications of AI (4.02) and the lowest in system design (3.71). The strongest correlation with AI competency was perceived usefulness (r = 0.742), and the weakest was AI ethics (r = 0.432). The implications of this study highlight the need for a more systematic integration of AI into the TVET curriculum, continuous professional development for educators, and stronger collaboration with smart food industries to better prepare students with industry-relevant skills. The study recommends that AI education go beyond technical proficiency to include ethical reasoning and human-centered thinking to ensure students are equipped to thrive in an increasingly digitalized food service sector. The findings serve as a basis for curriculum improvement, AI-based industrial training programs, and support national efforts to enhance graduate employability in the era of Industry 5.0.